"He thinks he's failed": Representations of Christian Clergy in English Canadian Fiction. (December 2014) - Sorensen, Sue
This survey of clerical characters in Canadian English fiction from Ralph Connor (1901) toMarina Endicott (2008) indicates that our literary ministers, which have been very little studied, deviate significantly from British and American traditions. Writers such asSinclair Ross (1941), Margaret Laurence (1964), Robertson Davies (1970, 1981), and Warren Cariou (1999) present ministries that thrive when they are plural, communal, spontaneous, or feminine. Christian leadership in these books is surprising and eccentric, often shaped by pastors who do successful ministry in spite of themselves. Their lack of faith or confidence is often a key component of their ministries. Additionally, ministry arises from unexpected sources not sanctioned by ecclesiastical authority and is nevertheless effective and resilient.